Improvement of the Functional Properties of Bread and Bake Products - Ashurova Muhabbat Zoirovna; Sulaymanova Gulchehra Hakimovna; Ganiyeva Nasiba Hikmatovna (Zeta Repository, 2023)
A review of the literature on the production of bakery products is presented. Problems tasks promising directions of development of the industry as well as the use of whey in the production of bread are considered.